Christopher Isherwood - Wilde, Alan (Twayne Publishers, 1971)
Provides in-depth analysis of the life, works, career, and critical importance of Christopher Isherwood
Includes bibliographical references and index
Keywords: Isherwood; Christopher; Autobiographical fiction; English